2020
DOI: 10.1016/j.cell.2020.11.033
|View full text |Cite
|
Sign up to set email alerts
|

LC3-Associated Endocytosis Facilitates β-Amyloid Clearance and Mitigates Neurodegeneration in Murine Alzheimer’s Disease

Abstract: Our paper focused on the identification of LC3-associated endocytosis and the role of this pathway in the clearance of beta-amyloid and mitigation of neurodegeneration in Alzheimer's Disease. Following publication, we have identified two errors in the original version of the article. First, the same FACS plot for TMEM119 expression was inadvertently presented for both 5xFAD/Rubicon +/À and 5xFAD/Rubicon À/À as shown in Figure S5C. A revised version of the figure is shown below with the correct TMEM119

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
90
2
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(95 citation statements)
references
References 0 publications
2
90
2
1
Order By: Relevance
“…This, together with the lack of LC3B recruitment suggest that the MavC is not targeted by autophagy. Although LC3B is also involved in alternative processes like LC3‐associated phagocytosis (LAP) 35 and ‐endocytosis (LANDO), 36 to effectuate autophagy of Mav the MavC needs to be targeted by LC3B /autophagophores—which we did not observe.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…This, together with the lack of LC3B recruitment suggest that the MavC is not targeted by autophagy. Although LC3B is also involved in alternative processes like LC3‐associated phagocytosis (LAP) 35 and ‐endocytosis (LANDO), 36 to effectuate autophagy of Mav the MavC needs to be targeted by LC3B /autophagophores—which we did not observe.…”
Section: Discussioncontrasting
confidence: 57%
“…This, together with the lack of LC3B recruitment suggest that the MavC is not targeted by autophagy. Although LC3B is also involved in alternative processes like LC3-associated phagocytosis (LAP)35 and -endocytosis (LANDO),36 to effectuate autophagy of Mav the MavC needs to be targeted by LC3B /autophagophores-which we did not observe.Endosomal TLRs are recruited to endosomes, phagosomes, and lysosomes. Recent studies have revealed differential anterograde and retrograde trafficking of the endosomal TLRs to their target organelles 37,38.…”
contrasting
confidence: 63%
“…Utilizing macrophages from mice with an Atg5-de ciency in myeloid cells (Castillo et al, 2012;Zhao et al, 2008), we examined if Atg5-de cient macrophages could still phagocytose MP. Atg5 is involved in multiple steps in the autophagic process (Hanada et al, 2007;Mizushima et al, 1998;Noda et al, 2013;Sakoh-Nakatogawa et al, 2013) as well as LAP (Heckmann et al, 2019). In comparison to wild-type macrophages, the uorescence intensity of intracellular MP was not signi cantly different compared to Atg5-de cient macrophages suggesting no change in the amount of MP internalization (Fig.…”
Section: Internalization Of Mp By Macrophages Does Not Results In Mp Degradationmentioning
confidence: 92%
“…30,31 In Alzheimer's disease mice, a deficiency of LC3-associated endocytosis in microglia increases the production of proinflammatory cytokines in the hippocampus. 32 Impaired autophagy in microglia exacerbates dopaminergic neuron loss in an MPTP-induced mouse model of Parkinson's disease. 33 While restoring autophagic capacity in mucopolysaccharidosis IIIB (MPS IIIB), a murine model reveals improved clearance of autophagic vacuoles in microglia and reduces inflammation in the brain.…”
Section: Discussionmentioning
confidence: 99%